Assessing the Risk-Benefit Ratio of Scoliosis Surgery in Cerebral Palsy: Surgery Is Worth It. (4th April 2018) - Miyanji, Firoz; Nasto, Luigi A.; Sponseller, Paul D.; Shah, Suken A.; Samdani, Amer F.; Lonner, Baron; Yaszay, Burt; Clements, David H.; Narayanan, Unni; Newton, Peter O.
Abstract : Background: The true benefits of scoliosis surgery in cerebral palsy (CP) remain uncertain. Our aims were to determine the benefits of spinal fusion according to health-related quality of life (HRQoL) improvement at long-term follow-up and to explore the effect of surgery-related complications on clinical outcomes. Methods: The cases of consecutive patients who had Gross Motor Function Classification System (GMFCS) level-IV or V cerebral palsy with 5-year follow-up from a prospective, longitudinal, multicenter database were analyzed. Caregivers completed the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD) questionnaire and 4 Likert-type anchor questions preoperatively and at 1, 2, and 5 years of follow-up. Data on complications were collected prospectively. Preoperative CPCHILD scores were compared with postoperative scores at the 1, 2, and 5-year follow-up evaluations. Preoperative CPCHILD scores were compared with postoperative scores at the 1, 2, and 5-year follow-up evaluations using repeated-measures analysis of variance (ANOVA). Spearman correlation coefficient was used to explore the association between changes in the CPCHILD at 1, 2, and 5-year follow-up and the reported complications within the follow-up period. Similarly, a comparative analysis between the percentage distribution of the answers to the 4 anchor questions and the reported complications was also performed. Results: Sixty-nine patients with a mean age (and standard deviation) of 13.4 ± 2.6 years at enrollment were analyzed. The major Cobb angle was a mean of 81.9° ± 26.7° preoperatively and improved to a mean of 28.7° ± 14.4° at 2 years and 30.7° ± 15.3° at 5 years postoperatively. Significant improvements in CPCHILD personal care, positioning, and comfort domains were noted at all time points. The mean increase in the total score was 7.19 (p < 0.001) at 1 year, and the score gain was maintained at 2 and 5 years postoperatively. The overall complication rate was 46.4% at 1 year, 1.4% between 1 and 2 years, and 4.3% at 2 to 5 years postoperatively, with surgical intervention required in 6 patients within 1 year and in 2 additional patients within 5 years following scoliosis surgery. There was no correlation between complications and CPCHILD scores postoperatively at all time points, with the only exception of a weak correlation (ρ = –0.450, p = 0.002) with CPCHILD comfort score at 1 year after surgery. Conclusions: Scoliosis surgery in patients with CP leads to a significant improvement in HRQoL, which is maintained 5 years following surgery. The substantial complication rate does not correlate with HRQoL changes postoperatively, suggesting that the benefits of surgery outweigh the risks in this fragile population. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.